Coupling ex vivo electroporation of mouse retinas and luciferase reporter assays to assess rod-specific promoter activity. (July 2016) - Boulling, Arnaud; Escher, Pascal
Abstract: Ex vivo electroporation of mouse retinas is an established tool to modulate gene expression and to study cell type-specific gene expression. Here we coupled ex vivo electroporation to luciferase reporter assays to facilitate the study of rod-photoreceptor-specific gene promoters. The activity of the rod-specific proximal bovine rhodopsin promoter was significantly increased in C57BL/6J wild-type retinas at postnatal days 1 and 7 by 3.4-fold and 8.7-fold respectively. In C57BL/6J Nr2e3 rd7/rd7 retinas, where the rod photoreceptor-specific nuclear receptor Nr2e3 is not expressed, a significant increase by 2.5-fold was only observed at postnatal day 7. Cone-specific S-opsin promoter activity was not modulated in C57BL/6J wild-type and Nr2e3 rd7/rd7 retinas. Taken together, we describe an easily implementable protocol to assess rod-specific promoter activity in a physiological context resembling that of the developing postnatal mouse retina.